Cyber D’ Orange Cafe / Mohd Arman Abu Bakar … [et al.] - Abu Bakar, Mohd Arman; Mat Hassim, Hafizah; Ismail, Yunizar; Zainuddin, Hasnah Niza; Mohamad Pias, Rozi (2000)
Business entrepreneurship is very challenging. Each entrepreneur needs to be strong, confident, determine and also smart to grab any business opportunity. Government encourage public to use the internet widely in the future so the demand for internet premises are expected to increase and because of that reasons we are determine and confident to get involved in this type of business. We also hope to improve people (especially school children) knowledge about computerizing and information technology as we are going towards “vision 2020 Base on our research and observation, we found that our business location at No. 11, Jalan 1/4 of Bandar Baru Bangi ,43650 Selangor Darul Ehsan It is a very strategic location. It is because in terms of security and market, the location are strategically situated near Sekolah Menengah Jln. 3 Bandar Baru Bangi and also Bandar Baru Bangi Police Station. Furthermore, it is not far from UKM and UPM and as condition it is situated at housing area. Among the services that we are going to provide for our customer are Internet Surf, Scanner, Photostatting, Player station, Foods and drinks, we expect to be in full operation on 1 January 2004 and the name of our internet cafe is Cyber D’ Orange Cafe.